COVID-19-related policy changes for methadone take-home dosing: A multistate survey of opioid treatment program leadership. Issue 1 (1st December 2022) - Levander, Ximena A.; Pytell, Jarratt D.; Stoller, Kenneth B.; Korthuis, P. Todd; Chander, Geetanjali
Abstract: Background: In the United States, methadone for treatment of opioid use disorder is dispensed via highly-regulated accredited opioid treatment programs (OTP). During the COVID-19 pandemic, federal regulations were loosened, allowing for greater use of take-home methadone doses. We sought to understand how OTP leaders responded to these policy changes. Methods : We distributed a multistate electronic survey from September to November 2020 of OTP leadership to members of the American Association for the Treatment of Opioid Dependence (AATOD) who self-identified as leaders of OTPs. We asked study participants about how their OTP(s) implemented COVID-19-related policy changes into their clinical practice focusing on provision of take-home methadone doses, factors used to determine patient stability, and potential concerns about increased take-home doses. We used Chi-square test to compare survey responses between characterizations of the OTPs. Results : Of 170 survey respondents (17% response rate), the majority represented leadership of for-profit OTPs (69%) and were in a Southern state (54%). Routine allowances and practices related to take-home methadone doses varied across OTPs during the COVID-19 pandemic: 80 (47%) reported 14 days for newly enrolled patients (within past 90 days), 89 (52%) reported 14 days for "less stable" patients, and 112 (66%) reported 28 days for "stable" patients. Conclusions : We found that not all eligible OTP leaders adopted the practice of routinely allowing newly enrolled, "less stable, " and "stable" patients on methadone to have increased take-home doses up to the limit allowed by federal regulations during COVID-19. The pandemic provides an opportunity to critically re-evaluate long-established methadone and OTP regulations in preparation for future emergencies.